Islam: Origins · Practices · Holy Texts · Sacred Persons · Sacred Places by Matthew S. Gordon (Oxford: Oxford University Press, 2002. 112 pages.) (American Journal of Islam and Society, 2006)
In his book Islam: Practices · Holy Texts · Sacred Persons · Sacred Places,Matthew Gordon discusses the divinely revealed nature of Islam throughtexts, persons, times, and places. His book is a welcome addition to a newwave of introductory books written by western scholars who seek to presentIslam objectively to western readers. The book’s main argument is that, likeother monotheistic religions, Islam is based on a set of divine beliefs thatrevolve exclusively around perceiving God through His many signs. Thesemanifestations of God are evident in the religious texts, persons, times, andplaces that have figured in Islam since its inception. At the same time,Gordon argues that the Islamic tradition “is far from monolithic and is theproduct of many centuries of scholarship and internal debate” (p. 67). Thetarget audience of this book is general readers and beginners in the field whoare looking for a handy textbook on the subject.This slim book is divided into nine chapters, each of which ends witha commentary on a selected text that elucidates the theme discussed, andincludes a glossary, bibliography, and an index. Its style is clear and simple.As the most important source of Islam’s genealogy, the Qur’an plays amajor role in this study. In the first chapter, Gordon offers a brief historicalreview of Islam’s religious and political development. By presenting differentIslamic dynasties that ruled various parts of the world, the authorreveals how Islam reached non-Arab peoples, which explains the fact thatthe majority of today’s Muslims live in Southeast Asia rather than theMiddle East.In the second chapter, the author discusses the axis around which the setof Islamic beliefs and practices revolves. Gordon rightly argues that thedivinely revealed nature of Islam stems absolutely from God’s pivotal placein Islam. Specifically, he claims that “[t]he relationship between Muslimsand God is informed by three principles that derive directly from the Quran”(p. 24): the “divine unity of God (tawhid),” “prophecy (nubuwwa),” and the“last days (maad).” At the same time, Gordon highlights the differencesbetween Sunni and Shi`i Islam and also refers to two other principles thatare exclusive to the Shi`i tradition: imamate and divine justice. Gordon’s discussionof Sufism takes up a considerable part of this chapter because, for ...